(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Interpretazione musicale e interpretazione giuridica. Il rapporto tra religione, musica e diritto - 2. Innovazioni liturgiche e musicali nella Riforma di Lutero: il corale luterano - 3. La dimensione spirituale del canto nella riforma liturgica di Giovanni Calvino. Il Salterio ginevrino - 4. Liturgia e musica nella Chiesa riformata anglicana - 5. La musica quale elemento identitario delle Chiese riformate. Considerazioni conclusive. Lutheran Chorale, Calvinist Psalter, Anglican Anthem. Religious identities and liturgical music in the Protestant context ABSTRACT: The paper examines the function played by music in the normative interventions regarding the Lutheran, Calvinist and Anglican liturgy in particular. The plurality of interpretations of the evangelical message that led to the birth of the Churches of the Reformation, in fact, finds precisely in the specific ritual innovations, including musical ones, the representation of an identifying and distinctive theological conception with respect to the Church of Rome.